Language learner autonomy and language learning opportunities inside and outside classroom - Hoang, Nguyen Thu Trang (H. : ĐHQGHN, 2019)
This study aims at investigating the degree of control that non-English major frst-year students exercise over their learning processes, resources and contexts in and out of the classroom. Data were obtained from questionnaires with 63 students, 30-to-60-minute interviews with three students, and the researcher’s notes of her observation during classroom lessons. The results from quantitative analysis for Mean and frequency and content analysis for emerging themes of the data reveal variation among the learners and withing each learner regarding the degree of their control over their language learning processes and resources in different contexts of learning and using the language. This suggests the need of helping learners to create learning opportunities both inside and outside the classrooms.